Analisis Kontribusi Pajak Hotel, Pajak Hiburan Pajak Restoran pada Pendapatan Asli Daerah (PAD) Kabupaten Sidoarjo - Meda Valentina Cesarie; Dwi Suhartini (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The fluctuation of hotel tax revenue, entertainment tax, and restaurant tax in Sidoarjo Regency in 2016-2021 is an important phenomenon to be studied. The purpose of this research is to analyze how the contribution of taxes to PAD and the effectiveness of the collection in Sidoarjo Regency. This study uses a quantitative descriptive method using the contribution and effectiveness formula, and uses a qualitative descriptive method with primary data collection techniques in the form of observations, interviews, and documentation as well as secondary data containing local tax revenues and PAD to analyze the level of achievement of tax effectiveness. The results of this study indicate that the contribution from hotel taxes, entertainment taxes, and restaurant taxes to the PAD of Sidoarjo Regency in 2016-2021 is still in the very less category because the growth of PAD revenue is greater than the growth of local taxes. In addition, tax revenue is also influenced by the lack of awareness of taxpayers as well as the national Covid-19 outbreak in 2020 and 2021 which limits people's mobility. In its tax collection, Sidoarjo Regency is already in the effective category because the expected realization is in accordance with the specified target by making it easier for taxpayers to report and deposit their bills online.